2017
DOI: 10.1016/j.jsxm.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Medical Male Circumcision Is Associated with Improvements in Pain During Intercourse and Sexual Satisfaction in Kenya

Abstract: BackgroundTwo cohort studies using data from randomized controlled trials in Africa offer the best evidence to date on the effects of voluntary medical male circumcision (VMMC) on male sexual function and satisfaction, suggesting no significant impairments in sexual function or satisfaction and some improvements in sexual function after male circumcision.AimTo assess the effects of VMMC on sexual function and satisfaction in a large population-based cohort of men circumcised as adults and uncircumcised control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The relationship between circumcision and sexual function has also been explored in various research studies, with conflicting findings. Some studies indicate that circumcised men have improved penile sensitivity and sexual satisfaction . Some, however, suggest the opposite with decreased penile sensitivity and sexual dysfunction .…”
Section: Techniques For Circumcisionmentioning
confidence: 99%
“…The relationship between circumcision and sexual function has also been explored in various research studies, with conflicting findings. Some studies indicate that circumcised men have improved penile sensitivity and sexual satisfaction . Some, however, suggest the opposite with decreased penile sensitivity and sexual dysfunction .…”
Section: Techniques For Circumcisionmentioning
confidence: 99%
“…This finding contradicts arguments based on low-quality evidence. 120 Nordstrom et al, 124 Kigozi et al, 125,149 Krieger et al 126…”
Section: Resultsmentioning
confidence: 99%
“…123 A case-control study in Kenya found that circumcised men reported less pain during sexual intercourse than uncircumcised control men during 2 years of follow-up. 124 Other aspects of sexual function did not differ between circumcised and uncircumcised men. Included in each review were 2 RCTs, 125,126 which are regarded as high-quality evidence.…”
Section: Sexual Functionmentioning
confidence: 87%
See 2 more Smart Citations